Systematic review of the qualitative literature on return to work after injury - MacEachen, Ellen; Clarke, Judy; Franche, Renée-Louise; Irvin, Emma; 10.5271/sjweh.1009, Workplace-based Return to Work Literature Review GroupM3 -. doi: (Scandinavian Journal of Work, Environment & Health, 2006)
' ' OBJECTIVES ': 'This paper reports on a systematic review of the international qualitative research literature on return to work. This review was undertaken in order to better understand the dimensions, processes, and practices of return to work. Because return to work often includes early return before full recovery while a person is undergoing rehabilitation treatment, physical recovery is embedded in complicated ways with workplace processes and practices and social organization. These process-oriented dimensions of return to work are well described in the qualitative literature. ' ' METHODS ': 'This systematic review of the literature covered peer-reviewed papers that focused on musculoskeletal and pain-related injuries and were published in English or French between 1990 and 2003. Findings from papers meeting relevance and quality criteria were synthesized using the meta-ethnographic approach. ' ' RESULTS ': 'This review found that return to work extends beyond concerns about managing physical function to the complexities related to beliefs, roles, and perceptions of many players. Good will and trust are overarching conditions that are central to successful return-to-work arrangements. In addition, there are often social and communication barriers to return to work, and intermediary players have the potential to play a key role in facilitating this process. ' ' CONCLUSIONS ': 'This paper identifies key mechanisms of workplace practice, process, and environment that can affect the success of return to work. The findings illustrate the contribution that qualitative literature can make to important aspects of implementation in relation to return to work.
Keywords: injury; meta-ethnographic approach; occupational health; qualitative literature; return to work; review; social relations; synthesis; systematic review; work organization